PENGARUH KECERDASAN EMOSIONAL TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS X IPS DI SMAN 3 KOTA JAMBI - Sari, Intan Maya; Kasiono, Kasiono (Universitas Batanghari Jambi, 2022)
The study, entitled The Effect of Emotional Intelligence on Student Learning Outcomes in Economics Subject Class X Social Sciences at SMAN 3 Jambi City, was conducted with the aim of knowing the effect of emotional intelligence on learning outcomes in economic subjects. This research was conducted at SMAN 3 Jambi City which was held in January 2022. The method used in this study is a quantitative approach. Sampling was done by simple random sampling technique. The sample used was 47 people who were taken randomly, class X IPS 1,2,3 were 90 students, the research instrument used was an emotional intelligence questionnaire, learning outcomes test in the form of grades, interviews, and documentation. Based on of 1.258, it shows that there is no influence of the independent variable (x) on the dependent variable (y). Based on the SPSS output table with the title model summary, it can be determined that the correlation coefficient value of the influence of emotional intelligence on student learning outcomes is 0.184 (R) with (R Square) 0.034 which is determined by the formula KD = 2 x 100% (KD = 0.034 x 100%) to 34%. In this study there is a low level of relationship. In the alternative hypothesis (Ha) proposed rejected and accepted the null hypothesis (Ho) . it means that there is no influence of emotional intelligence on student learning outcomes in economics subjects at SMAN 3 Jambi City. Keywords: Emotional Intelligence, Learning Outcomes